2001
DOI: 10.1103/physrevb.64.144510
|View full text |Cite
|
Sign up to set email alerts
|

Multiple magnetization peaks in weakly pinnedCa3Rh4Sn13

Abstract: The second magnetization peak and the peak effect anomaly coexisting in a given isothermal magnetization hysteresis loop show striking similarities in Ca 3 Rh 4 Sn 13 , a low-T c superconductor and YBa 2 Cu 3 O 7Ϫ␦ , a high-T c superconductor. The observed variation of the hysteresis width with field could imply a modulation in the degree of the plastic deformation of the elastic vortex solid. The characteristics of the high-T c cuprates, such as large Ginzburg number, short coherence length, decoupling of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…In our case, h max ¼ 0.4, indicating that point pinning alone cannot explain the pinning mechanism in the BaFe 1. 9 23 In the case of BaFe 1.8 Co 0.2 As 2 , a peak at h max % 0.45 was suggested to be related to the inhomogeneous distribution of Co ions. 31 In particular, the fact that, in our case, the maximum in F p occurs at h < 0.5 indicates that the pinning centres in BaFe 1.9 Ni 0.1 As 2 are of the dl type, while for dT c pinning, it is expected that the maximum would occur at h > 0.5.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In our case, h max ¼ 0.4, indicating that point pinning alone cannot explain the pinning mechanism in the BaFe 1. 9 23 In the case of BaFe 1.8 Co 0.2 As 2 , a peak at h max % 0.45 was suggested to be related to the inhomogeneous distribution of Co ions. 31 In particular, the fact that, in our case, the maximum in F p occurs at h < 0.5 indicates that the pinning centres in BaFe 1.9 Ni 0.1 As 2 are of the dl type, while for dT c pinning, it is expected that the maximum would occur at h > 0.5.…”
mentioning
confidence: 99%
“…In conventional low temperature superconductors, e.g., MgB 2 , 7 Nb 3 Sn, 8 etc., SMP corresponds to a hump feature in J c (B) far below the B c2 while peak effect (PE) is realized to happen near B c2 . 9 It is suggested that the PE is associated with the rapid softening of the flux line lattice. 10 In high temperature superconductors, different mechanisms including inhomogeneity of the sample, 11 Dynamic effects, 12 structural phase transition in the vortex lattice, 13 vortex order-disorder phase transition, 14,15 and cross over from elastic to plastic creep 16 have been proposed to explain the SMP.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Owing to the possibility of a sudden proliferation of dislocations on progressively increasing the magnetic field at a constant temperature, the quasi -long range ordered BG phase is anticipated [1,2] to transform first into a multi -domain (partially disordered) vortex glass (VG) phase. Such a transition usually reflects as a second peak in (isothermal) magnetization (M -H) loops, termed as the second magnetization peak (SMP) anomaly [5][6][7][8][9][10][11]. Thereafter, at elevated fields closer to the upper critical field (H c2 (T )), there occurs another anomaly, known as the quintessential peak effect (PE) phenomenon [3,9,10,[12][13][14][15][16][17][18] in field/temperature variation in critical current density, j c (H, T ).…”
Section: Introductionmentioning
confidence: 99%